Peningkatan Gizi Seimbang dan Deteksi Tumbuh Kembang pada Anak di Masa Pandemi Covid 19 - Liza Wati; Wasis Pujiati; Meily Nirnasari (Jurnal Abdimas Kesehatan (JAK), 2021)
Covid-19 is still not over, this triggers parental concern about the threat of covid-19 to children. For this reason, maintaining immunity is the main concern of parents at this time, one of which is through adequate nutritional intake for children and the importance of early detection of development and growth. growth in toddlers. The purpose of this community service is to increase knowledge related to balanced nutrition in infancy, measurement of weight and height and detection of growth and development using a developmental questionnaire. The method used in the form of counseling, weighing and detecting growth and development with a pre-screening development questionnaire. The result of this activity is increased knowledge related to balanced nutrition, and based on height/age measurements, 1 child is very short and 3 children are short. The next hope is for mothers of toddlers to provide balanced nutrition for the growth and development of their toddlers